2017
DOI: 10.1016/j.bbalip.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Fatty-acyl chain profiles of cellular phosphoinositides

Abstract: Phosphoinositides are rapidly turning-over phospholipids that play key roles in intracellular signaling and modulation of membrane effectors. Through technical refinements we have improved sensitivity in the analysis of the phosphoinositide PI, PIP, and PIP2 pools from living cells using mass spectrometry. This has permitted further resolution in phosphoinositide lipidomics from cell cultures and small samples of tissue. The technique includes butanol extraction, derivatization of the lipids, post-column infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(129 citation statements)
references
References 64 publications
4
125
0
Order By: Relevance
“…In this case, basal PIP 2 may suffice to localize GRKs. Although it generates diffusible G βγ , the WT M 1 R is phosphorylated by CK2 instead of GRK2/3 possibly because it substantially reduces plasma membrane PIP 2 and PIP with the strong stimuli that we use (20,45).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, basal PIP 2 may suffice to localize GRKs. Although it generates diffusible G βγ , the WT M 1 R is phosphorylated by CK2 instead of GRK2/3 possibly because it substantially reduces plasma membrane PIP 2 and PIP with the strong stimuli that we use (20,45).…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies with either supplementation of arachidonate or other PUFAs and the effect of serum starvation on cellular function (18). In such studies a remarkable effect of depletion of arachidonic acid has been noted (19). Current recommendations for cell culture suggest changing culture media (resupply of PUFAs) only as frequently as 3 days with no suggestion that this period of time could lead to important biochemical changes by depletion of PUFAs (20).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It has also been shown that in mouse embryonic fibroblasts and NIH 3T3 cells 18:0/20:4 PI species were the most abundant . More recent information using improved methodology confirms these findings and concludes that 50–80% of PI/PIPn have 18:0/20:4 acyl chains ( Figure ) …”
Section: Pi/pipn Acyl Chain Profile In Mammalsmentioning
confidence: 78%
“…Some phospholipids present predominant acyl chains in a tissue‐specific manner; for instance, in mammalian heart cardiolipin has predominantly four linoleoyl (18:2) acyl chains . However, PI 18:0/20:4 acyl chain enrichment seems ubiquitous to the whole organism in mammals, with the exception of lamb liver . The presence of PI enriched with specific acyl chains has been shown to be present across taxonomy; although, the specific molecular species varies …”
Section: Pi/pipn Acyl Chain Profile In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation